2005
DOI: 10.1001/archotol.131.7.571
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radial Forearm With Fibula and Scapula Osteocutaneous Free Flaps for Oromandibular Reconstruction

Abstract: To compare our experience with the osteocutaneous radial forearm free flap (group 1) (n=108) with other commonly used osteocutaneous free flaps (group 2) (n=56) such as the fibula and scapula in single-stage oromandibular reconstruction.Design: Retrospective case review.Setting: Tertiary-care academic medical center.Patients: One hundred sixty-three consecutive patients who underwent 164 mandibular reconstructions with osteocutaneous free flaps.Main Outcome Measures: Assessment of preoperative and intraoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 19 publications
7
93
3
1
Order By: Relevance
“…11 Proponents of the flap site the length and quality of bone stock available and the ease at which dental implants can be placed. Several studies however, have shown future dental implantation is infrequent in this patient population 9,12 and can be achieved with bone augmentation in OCRFFF reconstruction. 9 The thin pliable nature of the radial forearm flap with its superior soft tissue characteristics and lack of bulk allows for reconstruction of a variety of head and neck defects and prophylactic plating of the radius has reduced donor site morbidity associated with its use.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…11 Proponents of the flap site the length and quality of bone stock available and the ease at which dental implants can be placed. Several studies however, have shown future dental implantation is infrequent in this patient population 9,12 and can be achieved with bone augmentation in OCRFFF reconstruction. 9 The thin pliable nature of the radial forearm flap with its superior soft tissue characteristics and lack of bulk allows for reconstruction of a variety of head and neck defects and prophylactic plating of the radius has reduced donor site morbidity associated with its use.…”
Section: Discussionmentioning
confidence: 94%
“…As a result, the OCRFFF has steadily gained popularity in mandibular reconstruction. 9,[12][13][14] In the present study we evaluated outcomes in patients undergoing free flap reconstruction of lateral segmental mandibular defects. Patients reconstructed with the OCRFFF required shorter hospital stays and demonstrated equivalent wound healing and functional results when compared to patients who underwent fibula free flap reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] Our complication rates, and those previously reported in the literature, are summarized in Table 3. A previous publication by Militsakh et al 10 reports a retrospective review of patients from the University of Kansas Medical Center undergoing OCRFFF. Our 2 studies overlap slightly (2000)(2001)(2002)(2003); 50 patients were included in the present study and in the previously published article.…”
Section: Commentmentioning
confidence: 99%
“…24,26) The fibular flap has excellent bone quality and quantity, up to 25 cm, of sufficient pedicle length. 23,26,27) Furthermore, the complication rates and donor site morbidity have generally been acceptable. The disadvantages of the flap are its associated skin paddle, which is of somewhat limited size and flexibility, 23,26) and the limited bone height availability of the osseointegrated implant flap.…”
Section: Carcinoma Involving the Mandiblementioning
confidence: 99%